Polychaetes from the northern part of the Sea of Marmara with the description of a new species of Polydora (Annelida: Polychaeta: Spionidae) - ÇINAR, M. E.; DAĞLI, E.; ÇAĞLAR, S.; ALBAYRAK, S. (Mediterranean Marine Science, 2015)
Soft-bottom material collected from the northern part of the Sea of Marmara (off Küçükçekmece) included a total of 67 species belonging to 24 polychaete families. Three species (Brania pusilla, Lysidice cf. margaritacea and Sabellaria spinulosa) are new records for the Sea of Marmara. Three alien species (Polydora cornuta, Prionospio pulchra and Pseudopolydora paucibranchiata) were found at the shallow-water stations. Different polychaete assemblages occurred in the area and the mud percentage of sediment and salinity were the main factors related to their distribution. A new Polydora species, which is mainly characterized in having brownish pigmentation solely on the antero-dorsal sides of the body, and falcate major spines with only a bulge (anterior ones) or with a bulge and a small tooth, is described.